MINANGKABAU TRADITIONAL WOMEN'S CREATIVITY IN TRADITIONAL CERAMIC ARTS IN GALOGANDANG BATUSANGKAR - PURWO PRIHATIN; YANDRI YANDRI; SUMADI SUMADI (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
Galogandang women have the ability to create traditional ceramic art. Their  creativity  gave birth to a traditional ceramic form that had an impact on traditional women in relation to art. In this case, the presence of creative women in Galogandang gave birth to innovative traditional ceramics.   Traditional ceramic art was created in the form of pottery such as belango, pot, tirih pot, mengu, kumbuak, pot sigulamine, rosewater container, borasan, teapot, cauldron, kawa holder, miniature traditional house, giriak pot, pancake place, bika pot, tenpat water, incense sticks, carano pottery, miniature legged pan, glass, piggy bank, ashtray and so on. The problem formulated in this research is to explain the creativity of Galogandang women in developing the ceramic crafts to demonstrate their independence. This study uses a qualitative research method with descriptive analysis. In the end, the position of traditional women in their relationship with art is one of the spearheads in cultivating traditional arts and at the same time preserving pottery culture in Galogandang